Comparison of adolescent mental health in monogamy and polygamy families - Khosravi Shastan, Aziz ollah; Rajaei, Ali Reza; Teymouri, Saeed (Social Determinants of Health, 2023)
Background: Family shapes children's mental health and is a safe environment to ensure their mental health. This study aimed at comparing the mental health of adolescents in monogamy and polygamy families based on maternal psychological, economic, and social variables. Methods: This is a causal-comparative study, which was carried out on all adolescents aged 14-18 years old in the monogamy and polygamy families of Saravan city in the academic year of 2020-2021 with their mothers. Two hundred forty people were selected by convenience sampling method. Goldberg and Hillier General Health Questionnaire, Ghodrat-Nama Socioeconomic Status Questionnaire, and Drogaits Symptom Check list-90-Revised (SCL-90-R) were used. SPSS-26 was used to analyze the data. The results were analyzed using independent t-test, and multivariate analysis of variance. Results: The results showed that there was a significant difference between the mental health of adolescents in monogamy and polygamy families (P=0.034). Adolescents in monogamy and polygamy families were significantly different in only one component of mental health which is hostility (P<0.05), but in terms of other components there were no significant differences (P>0.05). Adolescents in polygamy families had lower mental health than children of monogamy families with moderate mental symptoms (P=0.003). Moreover, the high socio-economic status of mothers brought about a significant difference in adolescents' mental health (P=0.020). Conclusion: According to the results, the mental health and socio-economic status of mothers affect the mental health of adolescents, so comprehensive programs to promote mental health and attention to the socio-economic status of mothers can increase it in adolescents.